Diel Variability of CO2 Emissions From Northern Lakes. Issue 10 (5th October 2021) - Rudberg, D.; Duc, N. T.; Schenk, J.; Sieczko, A. K.; Pajala, G.; Sawakuchi, H. O.; Verheijen, H. A.; Melack, J. M.; MacIntyre, S.; Karlsson, J.; Bastviken, D.
Abstract: Lakes are generally supersaturated in carbon dioxide (CO2 ) and emitters of CO2 to the atmosphere. However, estimates of CO2 flux ( F CO 2 ) from lakes are seldom based on direct flux measurements and usually do not account for nighttime emissions, yielding risk of biased assessments. Here, we present direct F CO 2 measurements from automated floating chambers collected every 2–3 hr and spanning 115 24 hr periods in three boreal lakes during summer stratification and before and after autumn mixing in the most eutrophic lake of these. We observed 40%–67% higher mean F CO 2 in daytime during periods of surface water CO2 supersaturation in all lakes. Day‐night differences in wind speed were correlated with the day‐night F CO 2 differences in the two larger lakes, but in the smallest and most wind‐sheltered lake peaks of F CO 2 coincided with low‐winds at night. During stratification in the eutrophic lake, CO2 was near equilibrium and diel variability of F CO 2 insignificant, but after autumn mixing F CO 2 was high with distinct diel variability making this lake a net CO2 source on an annual basis. We found that extrapolating daytime measurements to 24 hr periods overestimated F CO 2 by up to 30%, whereas extrapolating measurements from the stratified period to annual rates in the eutrophic lake underestimated F CO 2 by 86%. This shows the importance of accounting for diel and seasonal variability in lake CO2 emission estimates. Plain Language Summary: Considerable carbon cycling occurs within lakes, and carbon inputs from the catchment can be processed internally, stored in sediment and biomass or transported downstream. Additionally, carbon is exchanged with the atmosphere, resulting in lake uptake or atmospheric emission of carbon dioxide. Carbon dioxide exchanges from lakes have globally significant implications, but may be highly variable in time in ways that are not yet accounted for in emission estimates. Here, we estimated carbon dioxide exchange during multiple days and nights in three lakes with different nutrient levels during summer and autumn. For the most nutrient rich lake we also covered the period of water column mixing in autumn, which constitutes a critical time for carbon exchange. When carbon dioxide emission exceeded uptake, we found 40%–67% higher average exchange rates during daytime than nighttime. In contrast, the most nutrient rich lake experienced clear day‐night differences only after autumn mixing, when carbon dioxide emissions increased. We found that only using daytime measurements overestimated carbon dioxide emissions by up to 30%, and not accounting for autumn mixing underestimated carbon dioxide emissions by 86%. This shows the importance of accounting for day‐night and seasonal variability in lake carbon dioxide emission estimates. Key Points: CO2 emission was measured at 2–3 hr resolution for 1–2 months in three boreal lakes, using multiple automated floating chambers Consistently higher daytime emission was observed in all lakes, but in the eutrophic lake diel variability was limited to post‐lake mixing Accounting for diel variability of CO2 emission within stratified and mixed periods is important to improve estimates of aquatic emissions